Simulação Numérica da Humidade Ascensional em Edifícios Históricos - Mário Jorge Araújo Morais (2011)
Humidity, particularly rising damp, is one of the main causes of degradation of historical constructions. This type of humidity manifestation appears when the constituent materials of the walls exhibit high capillarity and these walls are in contact with water or wet soil. In this work different treatment techniques were analyzed, particularly the technique treatment named "wall base ventilation". With the help of an automatic calculation program, WUFI 2D 3.3, developed by "Fraunhofer Institut für Bauphysik", a sensibility study was done with the main goal to determinate the influence of some variables in the capillarity rise of different monolithic walls, namely the importance of porosity, climate, wall thickness, and introduction of a ventilation channel at the base of the wall. The main objective of this work was analyzed the influence in the capillarity rise of a ventilation channel at the base of the wall, by the evaluation of geometry, positioning and ventilation rate. KEYWORDS: Rising damp, Wall Base Ventilation, Numerical Simulation, Historical Buildings.